2013
DOI: 10.1089/thy.2012.0243
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and Functional Changes of Salivary Gland Dysfunction After Radioactive Iodine Ablation in a Murine Model

Abstract: Background: Ablation of the thyroid tissue using radioactive iodine (RAI) after the surgical removal of welldifferentiated thyroid cancer can induce radiation-related salivary gland (SG) dysfunction. However, in vivo changes of SGs after RAI administration in appropriate animal models are not well described in the literature. This study was undertaken to document morphometric and functional changes during the 12 months after RAI administration in a murine model of RAI-induced SG dysfunction. Methods: Four-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
23
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 22 publications
7
23
0
4
Order By: Relevance
“…10 In a previous study, we found RAI-induced histological SG changes such as acinar degeneration and pleomorphism, atypical ductal configuration, peri-acinoductal inflammation, and fibrosis. 4 In the present study, we found that MR sialography depicted abnormal ductal and parenchymal findings. Ductal configurations observed by MR sialography were consistent with those reported in our previous study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…10 In a previous study, we found RAI-induced histological SG changes such as acinar degeneration and pleomorphism, atypical ductal configuration, peri-acinoductal inflammation, and fibrosis. 4 In the present study, we found that MR sialography depicted abnormal ductal and parenchymal findings. Ductal configurations observed by MR sialography were consistent with those reported in our previous study.…”
Section: Discussionsupporting
confidence: 58%
“…3 We previously investigated histological changes in RAI-exposed SGs of mice and found that RAI induces marked parenchymal and ductal pathologic changes. 4 Conventional sialography and salivary scintigraphy (SSG) are generally used to evaluate SG hypofunction but this requires an invasive maneuver, and radiation exposure is inevitable for SSG and conventional sialography.Ha Young Lee and Jae-Yol Lim contributed equally to this work.Electronic supplementary material The online version of this article ( …”
mentioning
confidence: 99%
“…As salivary glands do not possess the ability to organify iodine, retention time of the thyroid-ablative dose of 131 I is limited. Thus, salivary glands are preserved, at least in part, as is their ability to accumulate 99m Tc-pertechnetate, while thyroidal uptake is completely eliminated, as was shown by whole-body and neck transaxial planar SPECT imaging by Choi et al [35]. …”
Section: Discussionmentioning
confidence: 90%
“…Radioactive iodine ( 131 I) therapy causes acute and late complications as a result of adverse effects of exposure to radiation on normal tissue. Late effects of radioactive iodine on salivary glands are characterized as damage to salivary ductal cells and extend deeply into the soft tissue, causing both parenchymal and vascular cell damage . The specific cellular mechanisms of radioactive iodine‐induced salivary gland injury remain poorly understood, but one of the pathologic effects is thought to be related to a variety of inflammatory mediators leading to fibrotic processes.…”
Section: Discussionmentioning
confidence: 99%
“…The ß‐radiation emitted by radioactive iodine ( 131 I) damages salivary glands that normally take up 131 I mediated by sodium‐iodide symporter in salivary gland ductal cells . In our previous animal study, we investigated the histological changes in radioactive iodine‐injured murine salivary glands and found that radioactive iodine induced significant parenchymal pathologies, such as atypical ductal configuration, periacinoductal inflammation, and fibrosis . Radioactive iodine‐induced salivary gland damage consequently leads to obstructive sialadenitis presenting recurrent swelling with or without pain during meals.…”
Section: Introductionmentioning
confidence: 99%